2023
DOI: 10.1097/mrr.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle mass index and fat mass index during rehabilitation for traumatic brain injury and stroke measured by bioelectrical impedance analysis

Abstract: Although malnutrition may negatively impact the outcomes of rehabilitation and increase the cost of care, there are still no valid nutritional assessment methods appropriate for specific groups of patients undergoing rehabilitation. This study aimed to determine if a multifrequency bioelectrical impedance is suitable for monitoring the changes in body composition of brain-injured patients for whom individualized nutritional goals were set during rehabilitation. Fat mass index (FMI) and skeletal muscle mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Strength and muscle mass in stroke patients: The association muscle mass and strength in stroke patients has been called into doubt by recent research, some of which have shown only a minor correlation. This implies that decreased muscle mass alone cannot account for muscular weakness, and that muscle strength should also be taken into account independently while treating stroke victims [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Strength and muscle mass in stroke patients: The association muscle mass and strength in stroke patients has been called into doubt by recent research, some of which have shown only a minor correlation. This implies that decreased muscle mass alone cannot account for muscular weakness, and that muscle strength should also be taken into account independently while treating stroke victims [22,23].…”
Section: Discussionmentioning
confidence: 99%